Ammonothermal Synthesis of Nitrides: Recent Developments and Future Perspectives. Issue 46 (26th March 2018) - Häusler, Jonas; Schnick, Wolfgang
Abstract: Nitrides represent an intriguing class of functional materials with a broad range of application fields. Within the past decade, the ammonothermal method became increasingly attractive for the synthesis and crystal growth of nitride materials. The ammonothermal approach proved to be eminently suitable for the growth of bulk III‐nitride semiconductors like GaN, and furthermore provided access to numerous ternary and multinary nitrides and oxonitrides with promising optical and electronic properties. In this minireview, we will shed light on the latest research findings covering the synthesis of nitrides by this method. An overview of synthesis strategies for binary, ternary, and multinary nitrides and oxonitrides, as well as their properties and potential applications will be given. The recent development of autoclave technologies for syntheses at high temperatures and pressures, in situ methods for investigations of crystallization processes, and solubility measurements by ultrasonic velocity experiments is briefly reviewed as well. In conclusion, challenges and future perspectives regarding the synthesis and crystal growth of novel nitrides, as well as the advancement of autoclave techniques are discussed. Abstract : Ticket to nitride : Within the last decade, the ammonothermal method was rediscovered as versatile synthetic tool for the preparation and crystal growth of nitride materials. This minireview illuminates the recent progress of GaN crystal growth and covers ammonothermal synthesis strategies for ternary and multinary nitrides and oxonitrides. The latest developments in ammonothermal research and future perspectives for the discovery of novel nitrides are discussed.